Feminist technical communication: apparent feminisms, slow crisis, and the Deepwater Horizon disaster - Clark, Erin, author; Utah State University Press, publisher (Colorado State University. Libraries, 2023)
Introduces the methods of feminist technical communication and argues that rhetorical feminist approaches are vital to the future of technical communication, using a methodological approach to systematically interrogate systems of power that operate based on hidden misogynies.--Provided by publisher.
Keywords: Feminism and rhetoric; Feminist theory -- Social aspects; Communication of technical information -- Social aspects; Technical writing -- Social aspects; Risk communication -- Social aspects